Rent And Musataha in Investmen Projects - Luqman Hasan Rasool; Husain Taufiq Faizilla (QALAAI ZANIST JOURNAL, 2023)
The change of the regime in Iraq from a centralized economic system to a market economy system and the rapid opening of Iraq and the Kurdistan Region to investors, especially foreign investors on the one hand, and the lack of experience among those wishing to invest on the other hand, led to the failure of investment laws to achieve their objectives and the emergence of many obstacles And problems in practical application, especially those related to the allocation of land for investment purposes. Allocation of land for investment purposes through lease and musataha involves a series of procedures, starting with obtaining an investment permit for the investment project and allocating suitable lands for it, and ending with arranging the lease or musataha contract with the investor according to the conditions and procedures stipulated in the investment laws. Therefore, this study attempted to clarify the issue of land allocation for the investment project by the competent authority, as well as clarifying the formulas contained in the law for land allocation, such as rent, lease ending with ownership, and musataha. Through our study, we found out the ambiguity of the provisions of the law on the one hand, and their lack of integration on the other hand, especially with regard to determining the procedures for allocating land for investment projects through rent and musataha. At the end of this research, we presented some treatments that would overcome many of the obstacles that stand in the way of successful land allocation and then investment operations, whether in Iraq or in the Kurdistan Region of Iraq.